Perceptions of Hostel Dwellers The Conversion of Hostels into Family Units - Mpehle, Zwelibanzi (Richtmann Publishing, 2012)
The establishment of hostels during the apartheid era was seen as immediate and long termsolution to accommodate black male migrant workers who were primarily from the SouthernAfrica region, who were contracted to work in the mines and industries. These hostels werebuilt next to townships that were designated as black residential areas located, far from thecities and towns that were inhabited by whites. These camps offered cheap and affordableaccommodation for the poor migrant workers who lived in forlorn poverty. The initiative of theNational Department of Housing in launching the Public Sector Hostels Re-DevelopmentProgramme with the initial funding of R325-million to change the deploring, congested andfilthy hostels into a clean habitation suited for occupation by families was embraced by hostelinmates as a critical government’s muscle to integrate them into local communities and makingthem more homely. This article argues that, although the government’s effort in convertinghostels into family units was seen as the right step in restoring human dignity and social fibrein muddled families, there are obstacles that make dreams of thousand hostel dwellers notrealised in good time.